Correlation between junior high school students’ weight and their family background - Zhao, Xiying; Liu, Peng (Frontiers in Public Health, 2025)
ObjectiveThe objective of the study was to understand the correlation between weight in junior high school students and the influencing factors within their families in order to provide suggestions for weight management that can improve their health and growth.MethodsThe study included 6,617 junior high school students from the China Education Panel Survey, conducted (CEPS) between 2014 and 2015. This selection was based on the criteria for adolescent overweight and obesity issued by the National Health Commission of the People’s Republic of China, along with the definition of the Chinese family environment used in previous studies. The chi-squared test was performed to compare the association between categorical independent variables and the dependent variable. A binary logistic regression model was utilized to analyze the family environmental factors influencing junior high school students’ weight.ResultsThe prevalence of overweight and obesity among junior high school students was 14.39%, with a higher rate observed in boys compared to girls. The multivariate binary logistic regression analysis showed that having a non-agricultural hukou, having parents employed as enterprise managers, and spending more than 2 h gaming on weekends were the primary risk factors for overweight and obesity among middle school students. In contrast, being a child with siblings and strict parental management of screen time were the main protective factors against overweight and obesity.ConclusionThe influence of family background on overweight and obesity in junior high school students cannot be ignored. The prevention and control of overweight and obesity should start with family health education to improve students’ health and growth.